2017
DOI: 10.1111/bjh.14915
|View full text |Cite
|
Sign up to set email alerts
|

Iron storage in liver, bone marrow and splenic Gaucheroma reflects residual disease in type 1 Gaucher disease patients on treatment

Abstract: Gaucher disease (GD) is a lysosomal storage disorder characterized by the storage of glycosphingolipids in macrophages. Despite effective therapy, residual disease is present in varying degrees and may be associated with late complications, such as persistent bone or liver disease and increased cancer risk. Gaucher macrophages are capable of storing iron and locations of residual disease may thus be detectable with iron imaging. Forty type 1 GD (GD1) patients and 40 matched healthy controls were examined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Recently, a boom of studies has shown the role of iron in multiple cancers’ progression, invasion, migration, and death [8,9,10], as the liver is the most common iron metabolism and storage organ. Hence, the carcinogenesis and metastasis of hepatocellular carcinoma are highly related to iron [11]. A study reported that the expression of several iron metabolism pathways and iron transport genes is significantly altered in HCC relative to normal liver tissue, leading to an accumulation of intratumoral iron [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a boom of studies has shown the role of iron in multiple cancers’ progression, invasion, migration, and death [8,9,10], as the liver is the most common iron metabolism and storage organ. Hence, the carcinogenesis and metastasis of hepatocellular carcinoma are highly related to iron [11]. A study reported that the expression of several iron metabolism pathways and iron transport genes is significantly altered in HCC relative to normal liver tissue, leading to an accumulation of intratumoral iron [12].…”
Section: Introductionmentioning
confidence: 99%
“…From an imaging standpoint, hyperferritinemia with iron deposition such as within the liver may appear on with increased attenuation on CT, signal drop-out on out-of-phase gradient T1-weighted MRI and low signal on T2*-weighted MRI [47]. A group of investigators highlighted substantial iron deposition (as indicated by R2* values) in treated Gaucher disease patients compared with controls [48]. However, the precise relationship between hyperferritinemia and visceral iron deposition is poorly understood in Gaucher disease and the subject of continued investigation.…”
Section: Imaging Of Gaucher Disease Involvementmentioning
confidence: 99%
“…DWI may also hold promise with some evidence of decreased vertebral marrow ADC reflecting increased cellularity corresponding with disease status [100]. Last, iron filtration in marrow has been quantified in Gaucher disease with elevated R2* values in femoral and vertebral marrow compared to matched healthy controls [48].…”
Section: Imaging Of Gaucher Disease Involvementmentioning
confidence: 99%
“…Furthermore, an inherent problem of all semi-quantitative MR-scores is the fact that bone marrow signal intensities result from several factors not only including Gaucher cell infiltration. Especially iron overload, which is sometimes present in patients with Gaucher disease [22] leads to lower signal intensities, which cannot be differentiated from Gaucher cell infiltration. However, all patients in this study had received long-term ERT, which significantly lowers hyperferritinemia and iron overload [24], thus, iron accumulation might play a subordinate role here.…”
Section: Study Limitationsmentioning
confidence: 99%